Surface integrity of alumina machined by electrochemical discharge assisted diamond wire sawing. (January 2018) - Wang, Jin; Guo, Y.B.; Fu, Cheng; Jia, Zhixin
Abstract: Alumina is difficult to cut due to its characteristics of high hardness, brittleness and electrical resistivity. Diamond wire sawing is one of the most widely used methods of cutting alumina. However, the material removal rate (MRR) needs to be improved with the increasing demand for alumina parts. In this paper, the MRR of alumina is increased through integrating electrochemical discharge with diamond wire sawing. The electrochemical discharge may bring variation to surface integrity and affect performance of the machined part. Therefore, this research focuses on a detailed investigation on surface integrity of alumina cut by electrochemical discharge assisted diamond wire sawing. Surface roughness, topography, recast layer, and elements of the machined surface are analyzed based on experimental results. The findings provide a valuable basis for the application of electrochemical discharge assisted diamond wire sawing.